A Review of Herbal Medications for the Treatment of Alopecia (International Journal of Ayurveda and Pharma Research, 2023)
Alopecia is a condition that causes baldness and hair loss. It is a medical disorder that causes hair loss, often from the scalp or head skin. There are several factors that might contribute to hair loss, including genetics, environment, pollutants, different drugs, nutritional deficiencies, etc. Hair loss condition is essentially divided into numerous groups based on hair loss pattern and its various causes. Hairs are the development of follicles that are present on our skin and are described as "increased epithelial structure created by the keratinization of germ cells" in the definition of hair. Herbal remedies are used both externally and inwardly to stop hair loss and early greying. Promises of improved hair growth and less hair loss. The foundation of all medical research is herbs. Since herbal medications have fewer negative side effects than synthetic treatments and more positive outcomes, almost 80% of individuals have started using them. Several synthetic therapies, including corticosteroids, dithranol, tretinoin, minoxidil, zinc, systemic cortisone, irritants, immunosuppressant’s, finasteride, and azelaic acid, are currently available to treat hair loss (androgenetic and areata), but none of these treatments have been shown to have positive and long-lasting effects on patients. These medications' synthetic side effects, such as erythema, scaliness, pruritus, dermatitis, itching, etc., are also linked to their usage. So, in order to address the issue of hair loss, we looked into nature's treasures and discovered a number of herbs that have a track record of successfully treating hair loss. These herbal medicines' claimed modes of action include improved scalp blood circulation, DHT and 5-Reductase blockers, aromatherapy, and nutritional support. Phyllanthus Emblica, Oscimum sanctum, allium cepa, allium sativum, Thea Sinensis, Eclipta alba, Cocas nucifera, Sesamum indicum, Centella asiatica, Terminalia Chebula, Emblica officinalis, and Trigonella Foenum graecum are a few examples of herbal medications used to treat alopecia.